Psychosocial effects of COVID-19 in Ecuadorian university professors - Cevallos Zambrano, Doris Patricia; Moreira-Choez, Jenniffer Sobeida; Lamus de Rodríguez, Tibisay Milene; Sánchez-Urdaneta, Adriana Beatriz (Revista de Ciencias Sociales, 2023)
The objective of this work is to analyze the psychosocial effects of COVID-19 on Ecuadorian university professors, for which a quantitative research of descriptive and correlational nature was developed. Two instruments were applied, based on the Depression, Anxiety and Stress Scales and the Burnout questionnaire to the selected sample, in three public universities of easy access and linkage with the researchers. The population consisted of professors with appointment: 682 from the Technical University of Manabí, 678 from the Lay University Eloy Alfaro de Manabí, and 131 from the State University of Southern Manabí, from which a sample of 246, 246 and 98 professors was selected respectively. From the results it is derived that depression, anxiety, and stress were configured in psychosocial effects, which have had an impact during the COVID-19 pandemic on the professors of the universities studied, due to the pressure originated by new emerging methodological structures, the acquisition of other competences associated to technology, health and the risks of contagion, death and by the pedagogical attention through virtuality, unexpectedly arisen in times of pandemic.